Translating Attine Ant Colony Architecture into Energy-Efficient Structural Frameworks - Mtaka, Sarieh; Taajan, Shakoor (Journal of Progress in Civil Engineering, 2025)
Since ages humans have been getting inspired and replicated nature in one way or the other. On Earth, ants are one of the many species that have survived through the process of evolution and adaptation by creating social colonies by building their nest underground by excavation. Each nest is species typical with the basic structural units being descending tunnels connecting compact, horizontal chambers of oval to lobed outline. The size, shape, number and arrangement of these basic elements may vary from species to species to attain the maximum efficiency in architecture. Similarly, our multi storeyed buildings also vary in size, shape, number of floors, etc. depending on the requirement of each individual building. These designs can become highly efficient in terms of energy usage and other building related services if they are inspired from nature. This paper aims to study and build interrelation between the ant nest architecture and the design of contemporary multi-storeyed buildings with respect to sustainable parameters. Case of Tower of Time skyscraper was studied and parallels were drawn on how the Ants’ nest may serve as an inspiration for efficient structure & layout, energy efficiency, circulation & future expansion and community & social interaction.